Increasing the Interest of Class X MIA-2 Students SMA NEGERI 3 Binjai in Physical Sports and Health Education Learning Through the Application of the Demontration Method in Academic Year 2021/2022 - Ismadi Kuncoro, Agus (Berpusi Publishing, 2023)
The problem in this research is how is the Interest of Class X MIA-2 Students of SMA Negeri 3 Binjai in Learning Physical Education Sports and Health through the Application of the Demonstration Method for the 2021/2022 Academic Year. The purpose of this study was to find out how the Interest of Class X MIA-2 Students of SMA Negeri 3 Binjai in Learning Physical Education Sports and Health through the Application of the Demonstration Method for the 2021/2022 Academic Year. This research was conducted on class X MIA-2 students at SMA Negeri 3 Binjai for four months from August to November 2021. The research subjects were 35 students consisting of 16 boys and 19 girls. This research is a classroom action research using 2 cycles which include: planning, implementing, observing, and reflecting. Data collection techniques using the documentation method, observation method, and questionnaire method. The results of the study concluded that the students' interest in taking part in sports and health physical education lessons in class X MIA-2 SMA Negeri 3 Binjai in the subject matter of short distance running and long jump using the demonstration method was in the medium category with the highest frequency being considered at the end of cycle II in the category medium and high with 12 students or 34.28%. Students' interest in participating in sports and health physical education lessons in class X MIA-2 SMA Negeri 3 Binjai was in the very high category 3 students or 8.57%, low 8 students or 22.85%, while the cognitive aspects in cycle I obtained an average score -an average of 64.29 with the number of students who completed 20.57.